Puna (Argentina) and northern Chile Ordovician basic magmatism: A contribution to the tectonic setting - Coira, Beatriz Lidia Luisa (2009)
Geochemical characteristics of Ordovician basic volcanic rocks help to define the evolving tectonic setting of the Argentine Puna and northern Chile. Four spatially distinct magmatic groups are defined on geological, petrographical, geochemical and isotopic bases, each associated with particular geodynamic environments. The Tremadoc western group of subalkaline low K tholeiites with arc and modified MORB like signatures represent early stages of a back-arc basin, where spreading was incipient. The Arenig western group, medium K calc-alkaline basalts to andesites have volcanic arc in transition to back-arc signatures. The Tremadoc subalkaline basalts of the eastern group have REE patterns similar to E-MORB and at the same time weak subduction characteristics suggesting a rather mature supra-subduction zone (SSZ) basin. In contrast, the Late Tremadocian-Arenig basalts of the same group have intra-plate signatures, interpreted as magmas that ascended along pull apart regions associated with a transtensional regime. The geochemical patterns were applied to correlate basic sequences of doubtful geological setting. So, basalts from Chile were related to the Tremadocian western group, where they represent a slightly more mature stage of spreading of the basin. Basic rocks from Pocitos and part of Calalaste represent pre-Ordovician records of a back-arc system similar to that of the Tremadoc western group. Clearly similar arc patterns to those of the Arenig western group allow extending the arc environment to the southern Puna. The Tremadocian basalts from the eastern group were related to metabasites from the southern Puna, as part of a back-arc environment at that time.